Pemberdayaan Masyarakat melalui Pembuatan Pisang Crispy sebagai Sosiopreneur Baru Usaha Produk Lokal di Desa Ngunut, Jumantono Karanganyar: Community Empowerment through the Making of Crispy Banana as a New Sociopreneur for Local Product Business in Ngunut Village, Jumantono Karanganyar - Prasditio, Alvien Gusti; Syawala, Adestra Ayub; Faizah, Aisyah Taqiyyah; Mardani, Alifia Cerista; Widodo, Ananda Rizky; Pamungkas, Camellius Dellelis Gitom; Hambali, Firyal Labibah; Sanni, Grefta Jassika; Azizah, Hafshah; Candraningtyas, Maheswari; Salsabila, Marshanda Eka; Kurniasari, Mayliana Eka; et al. (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Ngunut Village is located in West Karanganyar Regency, Central Java and 33.3 km far to the east of Surakarta City. This village is 485.57 ha large. The natural resources of Ngunut Village has a lot of diversification. Various agricultural products, especially plantations in Ngunut Village, include bananas. Community empowerment activities in Ngunut Village, it is carried out using the Focus Group Discussion method and training, with the target of PKK women in Ngunut Village which will later form a new sociopreneur that is more focused on the production of crispy bananas. The empowerment method used is a participatory approach. The results of the FGD obtained information that people’s knowledge about processed banana products into banana chips is still low, knowledge in managing a business is still low, there is no clear structure of the crispy banana business group. The results of community empowerment for the development of crispy banana products include training on making banana chips, and improving packaging so that the product can be marketed outside the Karanganyar area.